Meningkatkan Kreativitas dan Kecerdasan Anak melalui Kegiatan Olahraga di Sekolah Dasar - Warni, Dwi Sulistianing; Zahra, Nur Hidayani; Selviana Hutasuhut, Adelia; Ramadani Harahap, Bintang; Sidik Siregar, Fajar (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study aims to improve children's creativity and intelligence through sports activities in elementary school. Various physical activities that hone motor and social skills can support optimal child development. This research examines the application of sports in PJOK learning that can improve students' kinesthetic and interpersonal intelligence. Based on the literature review, sports such as cheerful gymnastics, traditional games, and group activities can stimulate motor skills and social intelligence. The method used was an experiment with observation and pretest-posttest data analysis on elementary school students. The results showed a significant increase in students' kinesthetic and interpersonal intelligence after participating in the sports program. This study concludes that well-structured sports can be an effective means of improving children's creativity and intelligence in elementary school.